Additions to the orchid flora of Bhutan III : Paphiopedilum x pradhanii - Dorji, Phub
Paphiopedilum × pradhanii, a natural hybrid between P. fairrieanum (subgenus Paphiopedilum, section Ceratopetalum) and P. venustum (subgenus Paphiopedilum, section Barbata), is reported for the first time from Bhutan. Detailed geographical distribution, ecology, taxonomic notes, and dichotomous keys to all Paphiopedilum species found in Bhutan are provided. Additionally, a brief description of the parent species of this hybrid is provided.